εὐεργεσία, εὐεργέτης y εὐεργετέω EN SEPTUAGINTA Y EN EL NUEVO TESTAMENTO (Argos, 2024)
The noun euergesía can be traced back to Homer and found in several classical authors. However, it is resignified along with the verb euergetéo in the Septuagint, where both are mostly applied to God. In the Hellenistic period, euergétes is frequently used as a title of sovereigns and prominent personalities, and all three words acquire a distinctive nuance in the New Testament. This article will analyze the meanings of these terms within their contexts of use in the Septuagint and in the NT, aiming to inquire the process of resemantization they underwent, which allows to posit that they have clearly gained a religious and theological sense in these texts.
Keywords: euergesía; euergétes; euergetéo; Septuagint; New Testament